Downregulation of Runx2 by 1,25-Dihydroxyvitamin D(3) Induces the Transdifferentiation of Osteoblasts to Adipocytes - Kim, Jung Ha (Int J Mol Sci, 2016)
1,25-Dihydroxyvitamin D(3) (1,25(OH)(2)D(3)) indirectly stimulates bone formation, but little is known about its direct effect on bone formation. In this study, we observed that 1,25(OH)(2)D(3) enhances adipocyte differentiation, but inhibits osteoblast differentiation during osteogenesis. The positive role of 1,25(OH)(2)D(3) in adipocyte differentiation was confirmed when murine osteoblasts were cultured in adipogenic medium. Additionally, 1,25(OH)(2)D(3) enhanced the expression of adipocyte marker genes, but inhibited the expression of osteoblast marker genes in osteoblasts. The inhibition of osteoblast differentiation and promotion of adipocyte differentiation mediated by 1,25(OH)(2)D(3) were compensated by Runx2 overexpression. Our results suggest that 1,25(OH)(2)D(3) induces the transdifferentiation of osteoblasts to adipocytes via Runx2 downregulation in osteoblasts.